Post-Pandemic Shifts in English Language Teaching: Challenges and Perceptions in Online Learning Environments - Budiarta, I Komang; Krismayani, Ni Wayan (VELES Voices of English Language Education Society, 2024)
Online learning has significantly transformed lecturers' methodologies and students' learning experiences in English Language Teaching (ELT). This qualitative case study explores the perceptions and challenges of online ELT in the post-pandemic context, aiming to inform the design of effective future online learning environments. Data were gathered through document analysis, unstructured questionnaires, and semi-structured interviews with six lecturers and ninety students from the English Language Education Study Program at Universitas Mahasaraswati Denpasar. Findings indicate that online ELT has enhanced flexibility and accessibility, boosting learners' self-confidence and fostering self-directed and reflective learning through structured educational presentations. However, challenges persist, including the need for lecturers to maintain student engagement and provide effective feedback online, ensuring that even disengaged students participate actively. Additionally, the objectivity of online assessments and the technological divide are critical concerns. The study underscores the necessity of meticulously addressing these challenges and perceptions to cultivate more dynamic and inclusive online ELT classrooms in the future.